Creation of Engineering Drawing Learning Modules Using Datum Plane Media in Improving Students' Competence in Automotive Engineering Skills at SMK Negeri 55 Jakarta - Setiawan, Irwan (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The aim of this research is to determine the feasibility and effectiveness of the engineering drawing module using datum plane media to strengthen students' knowledge about projections on objects. This research uses the 4D research method developed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel in 1974 which consists of 4 stages, namely Define, Design, Develop and Disseminate. Data was collected through interviews, questionnaires and pre test-post test. The subjects of this research were students majoring in automotive engineering at SMKN 55 Jakarta 2023/2024 academic year class x semester 1 with a sample size of 30 students from a population of 3 classes totalling 103 students. The research began with Define, namely defining the need for difficulties in students' understanding of reading and drawing projections by observing and interviewing teachers who teach technical drawing. Furthermore, from the observation data obtained, the researchers looked for solutions to the problems faced by automotive vocational school students with modules that use datum planes, so the researchers designed the required modules and datum planes. At the Develop stage, the researcher's design is validated by material experts and media experts, their criticism and suggestions are used as input for revising the media created. Finally, the Disseminate media stage, which had been validated and revised, was used on 30 students from SMKN 55 Jakarta, carried out a pre-test-post test and obtained an average result for the entire pre-test sample of 45.33 and post-test of 68.17.